Acoustic dynamics in performance halls: Enhancing violin sound quality in the FPSD orchestra room - Daniel de Fretes; Fitriawati Fitriawati (Universitas Pendidikan Indonesia, 2024)
With an emphasis on improving violin sound quality, this study explores the acoustic dynamics of the FPSD Orchestra Room at Universitas Pendidikan Indonesia. Direct and reflected sound are the two factors that impact the phenomena of interior sound. This research emphasizes the crucial balance between sound absorption and reflection to optimize the acoustic environment and ensure clarity and richness in violin performances. Improving acoustic conditions is vital to increase audience experience and performance quality. The study used a qualitative descriptive research style combining literature review and observations. The research site was the FPSD Orchestra Room, renowned for its historical significance and contribution to music education. The observations revealed significant acoustic obstacles that adversely affected the violin sound's clarity, including excessive reverberation and unequal sound dispersion. The literature review revealed the theoretical underpinnings of sound propagation, reverberation, absorption, reflection, and diffraction. The acoustic environment can be greatly enhanced by introducing sound-absorbing materials to optimize reverberation duration, controlling reflections with diffusers, and utilizing adaptive acoustic systems. Furthermore, combining virtual acoustics technology with digital sound processing systems allows for dynamic control over acoustic parameters, increasing the performance space's adaptability. These improvements provide a customized acoustic environment that supports a variety of musical performances and guarantees the audience a clear, engaging auditory experience. This study emphasizes the significance of fusing cutting-edge technology innovations with conventional acoustic design concepts to attain optimal sound quality in performance halls. Innovation and research must never stop to improve these acoustic settings even further.